PERSEPSI TOKOH-TOKOH AGAMA TENTANG TOLERANSI ANTAR UMAT BERAGAMA DAN IMPLEMENTASINYA DI KOTA MAKASSAR - Munirah Munirah; Andi Amiruddin (IQRA : JURNAL PENDIDIKAN ISLAM, 2025)
Based on these problems, the objectives of the study are formulated as follows: (1) To identify the teachings of tolerance according to various religions, and (2) To analyze the perceptions of religious leaders regarding interreligious tolerance and its implementation in the city of Makassar.This study employs a descriptive qualitative and quantitative research design, using sociological, structural-functional phenomenological, and theological approaches. Data were collected through observation, interviews, documentation, and questionnaires, with a list of questions distributed to 34 respondents. The results of the study indicate that interreligious tolerance refers to a willingness to accept differences by fostering mutual understanding, mutual respect, and mutual appreciation in the practice of religious teachings, as well as cooperation in social life. Religious teachings that support the realization of interreligious tolerance are generally similar across religions, namely: first, all religions state that religion brings peace; second, all humans are brothers and sisters; third, all acknowledge the existence of other religions; and fourth, all motivate their adherents through various guidelines and examples on how to respect, appreciate, and cooperate with others regardless of their religion. Keywords: Perceptions of Religious Leaders, Interreligious Tolerance, and Its Implementation in the City of Makassar.